Trying to become a different type of company: dynamic capability at Smith Corona - Danneels, Erwin (Strategic Management Journal, 2011)
Abstract Smith Corona, formerly one of the world's leading manufacturers of typewriters, was challenged to exercise dynamic capability in the face of the dissipation of its main product category. A study of the last two decades of the life of the company shows how Smith Corona tried to alter its resource base by leveraging existing resources, creating new resources, accessing external resources, and releasing resources. Using the extended case method, this study advances dynamic capability theory by confronting it with an empirical case. The Smith Corona case provides rich insights into the resource alteration processes by which dynamic capability operates, and highlights resource cognition as a missing element in dynamic capability theory. Copyright © 2010 John Wiley & Sons, Ltd.